The First Acanthamoeba keratitis Case of Non-Contact Lens Wearer with HIV Infection in Thailand - Napaporn Tananuvat (2020)
© 2019, Korean Society for Parasitology and Tropical Medicine. Acanthamoeba keratitis (AK) is a rare sight-threatening corneal infection, often reporting from contact lens wearers. An asymptomatic human immunodeficiency virus (HIV)-infected Thai male without history of contact lens use complained foreign body sensation at his left eye during motorbike riding. He had neither specific keratitis symptoms nor common drugs responding, which contributed to delayed diagnosis. By corneal re-scraping, Acanthamoeba-like cysts were detected by calcofluor white staining and agar culture. The etiological agent obtained from the culture was molecularly confirmed by Acanthamoeba spp.-specific PCR, followed by DNA sequencing. The results from BLAST and phylogenetic analysis based on the DNA sequences, revealed that the pathogen was Acanthamoeba T4, the major genotype most frequently reported from clinical isolates. The infection was successfully treated with polyhexamethylene biguanide resulting in corneal scar. This appears the first reported AK case from a non-contact lens wearer with HIV infection in Thailand. Although AK is sporadic in developing countries, a role of free-living Acanthamoeba as an opportunistic pathogen should not be neglected. The report would increase awareness of AK, especially in the case presenting unspecific keratitis symptoms without clinical response to empirical antimicrobial therapy.